Balance of Payments Statistics Yearbook, 2015. (Balance of Payments Statistics; Balance of Payments Statistics, 2015)
This annual issue of Balance-of-Payments Statistics Yearbook (BOPSY) contains two sections: World and Regional Tables, and Country Tables. The first section presents 21 world and regional tables for major components of the balance of payments, net International Investment Position (IIP), and total financial assets and total liabilities for the IIP. The second section provides detailed tables on balance-of-payments statistics for 191 economies and IIP data for 150 economies. Volume 66 of the BOPSY, published by the IMF, contains balance of payments and international investment position (IIP) data in accordance with the sixth edition of the Balance of Payments and International Investment Position Manual. Data are presented for 2007 forward. The IMF is grateful for countries' cooperation in providing comprehensive, timely, and regular data to the IMF for re-dissemination. These data support the IMF's Statistics Department in its efforts to respond to the analytical and policy needs of the IMF, member countries, and the international community.